Poly [1,1'-bis(ethynyl)-4,4'-biphenyl(bis-tributylphosphine)Pt(II)] solutions used as low dose ionizing radiation dosimeter - Bronze-Uhle, E. S. [UNESP]; Batagin-Neto, A. [UNESP]; Fernandes, D. M. [UNESP]; Fratoddi, I.; Russo, M. V.; Graeff, Carlos Frederico de Oliveira [UNESP] (AIP Publishing, 2013)
In this work, the effect of gamma radiation on the optical properties of polymetallayne poly[1,1'-bis(ethynyl)-4,4'-biphenyl(bis-tributylphosphine)Pt(II) ] (Pt-DEBP) in chloroform solution is studied. The samples were irradiated at room temperature with doses from 0.01 Gy to 1 Gy using a 60Co gamma ray source. A new band at 420 nm is observed in the emission spectra, in superposition to the emission maximum at 398 nm, linearly dependent on dose. We propose to use the ratio of the emission amplitude bands as the dosimetric parameter. This method proved to be robust, accurate, and can be used as a dosimeter in medical applications. © 2013 AIP Publishing LLC.
Keywords: Chloroform solutions; Dosimetric parameter; Emission maxima; Emission spectrums; Gamma ray sources; Low dose; Radiation dosimeters; Room temperature; Emission spectroscopy; Gamma rays; Ionizing radiation; Medical applications; Platinum